2017
DOI: 10.1016/j.rmed.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing and second-line pulmonary function tests to detect obstructive pattern in symptomatic smokers with borderline spirometry

Abstract: In smokers with borderline spirometry, CPET and second-line pulmonary function tests may detect obstructive pattern. These subjects should be referred for second line testing, to obtain a diagnosis, or at least to clarify the mechanisms underlying symptoms. Whether the natural history of these patients is similar to COPD, and they deserve a similar therapeutic approach is worth investigating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…This accords with recent work showing that smokers with preserved FEV 1 had evidence of small airways damage, gas trapping, and impaired gas transfer. 23 , 24 Abnormality in single-breath nitrogen washout in symptomatic smokers and in MBW parameters in asymptomatic smokers (>10 pack years) has also been previously demonstrated. 24 , 25 The particular advantages of LCI as an outcome for assessing these early changes is that the methodology is standardized, 14 with good reproducibility, and with apparently good sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…This accords with recent work showing that smokers with preserved FEV 1 had evidence of small airways damage, gas trapping, and impaired gas transfer. 23 , 24 Abnormality in single-breath nitrogen washout in symptomatic smokers and in MBW parameters in asymptomatic smokers (>10 pack years) has also been previously demonstrated. 24 , 25 The particular advantages of LCI as an outcome for assessing these early changes is that the methodology is standardized, 14 with good reproducibility, and with apparently good sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…In line with previous FOT results in smokers and mild COPD patients, and in contrast with the study of Di Marco et al, the resistive parameters presented a highly significant increase (R0, R4, Rm; Table 1 ). 6 , 13 , 49 51 In the study of Shinke et al approximately 60% of the studied smokers showed elevated resistance. 52 Using an impulse-oscillation system, Frantz et al and Elbehairy et al showed that pulmonary resistance can indicate abnormalities earlier than conventional spirometric parameters, while Crim et al found increased resistance values in subjects with mild COPD.…”
Section: Discussionmentioning
confidence: 95%
“…The results of the present study are in line with this proposition, and with previous works showing that marked impairments were observed in subjects with mild airway obstruction and symptomatic smokers with borderline spirometry. 8 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…It can identify tobacco smokers at risk of developing chronic obstructive pulmonary disease (COPD) (Macklem, 1972) and has been validated against histopathological proven structural peripheral airway abnormalities in the human lung (Cosio et al, 1978), and remains the only ventilation inhomogeneity marker to be validated in this way. The N 2 VC SBW test remains in use in many laboratories today (Mikamo et al, 2013;Boeck et al, 2016;Di Marco et al, 2017), mainly because of its time-effectiveness, yet the correlation between N 2 MBW and N 2 SBW remains largely unknown, and remains an important gap in current knowledge for clinicians interested in inert gas washout techniques. The N 2 VC SBW test remains in use in many laboratories today (Mikamo et al, 2013;Boeck et al, 2016;Di Marco et al, 2017), mainly because of its time-effectiveness, yet the correlation between N 2 MBW and N 2 SBW remains largely unknown, and remains an important gap in current knowledge for clinicians interested in inert gas washout techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Specific to adult asthma, S III steepness correlates with disease severity as determined by asthma exacerbation frequency (Bourdin et al, 2006). The N 2 VC SBW test remains in use in many laboratories today (Mikamo et al, 2013;Boeck et al, 2016;Di Marco et al, 2017), mainly because of its time-effectiveness, yet the correlation between N 2 MBW and N 2 SBW remains largely unknown, and remains an important gap in current knowledge for clinicians interested in inert gas washout techniques.…”
Section: Introductionmentioning
confidence: 99%